2013
DOI: 10.7196/samj.6414
|View full text |Cite
|
Sign up to set email alerts
|

High uptake of Gardasil vaccine among 9 - 12-year-old schoolgirls participating in an HPV vaccination demonstration project in KwaZulu-Natal Province

Abstract: Corresponding author : I Moodley (moodleyi15@ukzn.ac.za) Background. Cervical cancer is linked to infection of the cervix by oncogenic human papillomavirus (HPV) subtypes. The quadrivalent Gardasil vaccine (against HPV types 6,11, 16, 18), recommended in girls 9 -12 years of age, has been shown to be safe, immunogenic and efficacious, with minimal or no side-effects. Aim. To demonstrate the capacity of school health teams to carry out vaccinations within a school environment. Objectives. To assess the uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 6 publications
3
78
0
Order By: Relevance
“…Moodley et al [15] reported overall HPV vaccine uptake in an implementation study in KwaZulu-Natal Province, SA, of 99.7%, 97.9% and 97.8% for the first, second and third vaccination doses, respectively. These data represent the uptake and completion rates of those who consented, but uptake as a proportion of girls available for vaccination was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Moodley et al [15] reported overall HPV vaccine uptake in an implementation study in KwaZulu-Natal Province, SA, of 99.7%, 97.9% and 97.8% for the first, second and third vaccination doses, respectively. These data represent the uptake and completion rates of those who consented, but uptake as a proportion of girls available for vaccination was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of completion were described in local governments of South Africa (97.8%), 70 Tanzania (78.7%), 76 and Brazil (73%). 68 All included an education campaign and free HPVV.…”
Section: Environmental Interventions: Big Policy Local Government Inmentioning
confidence: 99%
“…A pilot study conducted in 39 schools in KwaZulu-Natal province reported a high completion rate of three doses of HPV vaccination. 11 To make the vaccination a success, all stakeholders in the country need to contribute in this regard, and university academics have a significant role to play. For example, they can provide accurate knowledge to their students and recommend vaccinating against this preventable disease.…”
Section: Introductionmentioning
confidence: 99%